A novel vertical waterproofing joint with trapezoidal steel plate connections for steel–concrete underground silos: Bending test and numerical simulation. (July 2023) - Zhang, Hao; Wang, Hongkai; Yang, Jinping; Wang, Fuming
Graphical abstract: Highlights: A new waterproof prefabricated underground silos wall with TSP was proposed. Connection, atress and waterproof of prefabricated underground silos were solved. The optimal design measures of new joint with different parameters were put forward. The equation of flexural capacity under the different parameters was obtained. Abstract: Steel-concrete silo is a popular option in green grain storage project due to its pretty stiffness and better waterproof. However, the structural form and mechanical properties of vertical joints in the prefabricated steel–concrete silo are two key problems, which restrict its wide application. Consequently, a novel vertical waterproofing joint with trapezoidal steel plate (TSP) connections is proposed for steel–concrete underground silos. The TSP is welded laterally between the adjacent prefabricated silo walls, and it also needs to undertake part of the axial force transmission of underground silos. Firstly, the steel–concrete specimen of two-TSPs' deformation, interior force, failure mode and mechanism are analyzed comprehensively. Secondly, two numerical model of the steel–concrete silo wall with non-TSP and two-TSP are established on ABAQUS. Finally, the effect of different parameters on mechanical properties are analyzed. Experimental results show that, compared with the specimens with non-TSP, the deflection of the proposed two-TSP connection is decreased by 270% and the yield load of internal waterproof steel plate is increased by 29%. When the internal waterproof steel plate is yield, the compressive strain of external waterproof steel plate and TSP in the upper part are similar, while its internal tensile strain in the lower part have a little gap. TSP can cooperative work with both internal and external waterproof steel plates. Numerical results are difference from test results by only 5.34% and 4.48% respectively, which verifies that the numerical model is effective and feasible. Meanwhile, it is also found that the proposed novel connection has the greatest strength enhancement effect on flexural bearing capacity of vertical joint, and the greatest effect on improving the flexural bearing capacity of vertical joint.